2021
DOI: 10.1097/ipc.0000000000001037
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Skin Rash After Receiving SARS-CoV-2 mRNA Moderna Vaccine

Abstract: I n a year characterized by the dramatic and devastating global effects of a pandemic fueled by a new virus, the SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), it is not surprising that the announcement of an emergency use authorization for vaccines by the Food and Drug Administration was met with great hope and enthusiasm. It is abundantly clear that vaccines are needed-in addition to social distancing and masking-to prevent LETTER TO THE EDITOR e262 www.infectdis.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In cases where the same sample was used for more than one study, all studies were reviewed to determine the extent to which there may be duplication in the reported outcomes between studies. The full text of selected studies was reviewed, and data on demographics, article type, number of reported cases with cutaneous involvement, vaccine, and rash type (morphology) were extracted from articles texts, tables, figures, and summarized through a descriptive table (Table 1)…”
Section: Methodsmentioning
confidence: 99%
“…In cases where the same sample was used for more than one study, all studies were reviewed to determine the extent to which there may be duplication in the reported outcomes between studies. The full text of selected studies was reviewed, and data on demographics, article type, number of reported cases with cutaneous involvement, vaccine, and rash type (morphology) were extracted from articles texts, tables, figures, and summarized through a descriptive table (Table 1)…”
Section: Methodsmentioning
confidence: 99%
“…Most of COVID arm cases were not required medical treatment, followed by topical corticosteroids were used in 23 (2%) cases [6, 11, 16, 19, 24-27, 29, 32] and oral antihistamines in 23 (2%) cases [6, 11, 19, 25-27, 31, 32] were used. In contrast, others reported the administration of oral corticosteroids, antibiotics, and NSAIDs as a pain relievers [6,16,19,24,27,28,[31][32][33].…”
Section: Clinical Course and Prognosismentioning
confidence: 99%